Utility of the Nonabsorbed (<0.4%) Antibiotic Rifaximin in Gastroenterology and Hepatology - Su, Chinyu G. (Gastroenterol Hepatol (N Y), 2006)
Oral antibiotics have probable or documented therapeutic utility for multiple enteric conditions commonly treated by gastroenterologists and hepatologists, but they are not frequently prescribed. Barriers to antibiotic use include concerns about bacterial resistance, drug interactions, and antibiotic-associated side effects and toxicity, particularly in vulnerable populations. The use of minimally absorbed oral antibiotics has been suggested as an approach to overcoming some of these barriers, but minimally absorbed antibiotics have not been an important part of the US gastroenterologists’ or hepatologists’ armamentarium until recently. The 2004 introduction in the United States of the nonabsorbed (<0.4%) oral antibiotic rifaximin is cause for reassessing the potential usefulness of minimally absorbed oral antibiotics for bacterial enteric illness. Rifaximin has broad-spectrum in vitro antibacterial activity against enteric pathogens, gut-localized action, and minimal systemic absorption—a profile consistent with usefulness for a range of enteric conditions involving a pathogenetic role of bacteria. The emerging clinical profile of rifaximin also supports its potential utility for multiple enteric conditions. Rifaximin has a tolerability profile comparable to that of placebo and is not known to interact clinically with other medications. The efficacy of rifaximin is well documented for the treatment of infectious diarrhea caused by noninvasive pathogens and hepatic encephalopathy. A growing body of data supports the efficacy of rifaximin for additional enteric conditions, such as Crohn’s disease, ulcerative colitis, small-intestinal bacterial overgrowth, pouchitis, and antibiotic-associated colitis, that are characterized by acute bacterial infection or bacterial colonization. In addition, rifaximin has recently been demonstrated effective in the prevention of travelers’ diarrhea and shigellosis in controlled clinical studies. Ongoing studies and more experience with rifaximin in clinical practice will help to further define the role of this antibiotic in gastroenterology and hepatology.